Homozygous slc25a20 zebrafish mutant reveals insights into carnitine-acylcarnitine translocase deficiency pathogenesis - Ryuichi Hishida; Kohei Ishiguro; Tomoyuki Yamanaka; Shinya Toyokuni; Hideaki Matsui (Molecular Genetics and Metabolism Reports)
The SLC25A20 gene encodes carnitine-acylcarnitine translocase (CACT), facilitating the transport of long-chain acylcarnitine required for energy production via β-oxidation into the mitochondria. Loss-of-function mutations in this gene lead to CACT deficiency, a rare autosomal recessive disorder of fatty acid metabolism characterized by severe symptoms including cardiomyopathy, hepatic dysfunction, rhabdomyolysis, hypoketotic hypoglycemia, and hyperammonemia, often resulting in neonatal mortality. Here, we utilized CRISPR/Cas9 gene editing to isolate slc25a20 mutant zebrafish. Homozygous mutants displayed significant lethality, with the majority succumbing before reaching maturity. However, we identified a notably rare homozygous individual that survived into adulthood, prompting a histological examination. Firstly, we observed adipose tissue accumulation at various sites in the homozygous mutant. The mutant heart exhibited hypertrophy, along with degenerated myocardial and muscle cells containing numerous eosinophilic nuclei. Additionally, we found no large oil droplet vacuoles in the mutant liver; however, the hepatocytes displayed numerous small vacuoles resembling lipid droplets. Iron deposition was evident in the spleen and parts of the liver. Overall, our slc25a20 zebrafish mutant displayed tissue pathologies analogous to human CACT deficiency, suggesting its potential as a pathological model contributing to the elucidation of pathogenesis and the improvement/development of therapies for CACT deficiency.